Angiotensin-(1–7) Expressed From Lactobacillus Bacteria Protect Diabetic Retina in Mice - Verma, Amrisha (Transl Vis Sci Technol, 2020)
PURPOSE: A multitude of animal studies substantiates the beneficial effects of Ang-(1–7), a peptide hormone in the protective axis of the renin angiotensin system, in diabetes and its associated complications including diabetic retinopathy (DR). However, the clinical application of Ang-(1–7) is limited due to unfavorable pharmacological properties. As emerging evidence implicates gut dysbiosis in pathogenesis of diabetes and supports beneficial effects of probiotics, we sought to develop probiotics-based expression and delivery system to enhance Ang-(1–7) and evaluate the efficacy of engineered probiotics expressing Ang-(1–7) in attenuation of DR in animal models. METHODS: Ang-(1–7) was expressed in the Lactobacillus species as a secreted fusion protein with a trans-epithelial carrier to allow uptake into circulation. To evaluate the effects of Ang-(1–7) expressed from Lactobacillus paracasei (LP), adult diabetic eNOS(−/−) and Akita mice were orally gavaged with either 1 × 10(9) CFU of LP secreting Ang-(1–7) (LP-A), LP alone or vehicle, 3 times/week, for 8 and 12 weeks, respectively. RESULTS: Ang-(1–7) is efficiently expressed from different Lactobacillus species and secreted into circulation in mice fed with LP-A. Oral administration of LP-A significantly reduced diabetes-induced loss of retinal vascular capillaries. LP-A treatment also prevented loss of retinal ganglion cells, and significantly decreased retinal inflammatory cytokine expression in both diabetic eNOS(−/−) and Akita mice. CONCLUSIONS: These results provide proof-of-concept for feasibility and efficacy of using engineered probiotic species as live vector for delivery of Ang-(1–7) with enhanced bioavailability. TRANSLATIONAL RELEVANCE: Probiotics-based delivery of Ang-(1–7) may hold important therapeutic potential for the treatment of DR and other diabetic complications.